Effect of Inulin Source and a Probiotic Supplement in Pig Diets on Carcass Traits, Meat Quality and Fatty Acid Composition in Finishing Pigs - Eugeniusz R. Grela; Małgorzata Świątkiewicz; Mariusz Florek; Maciej Bąkowski; Grzegorz Skiba (Animals, 2021)
In this experiment, we investigated the effect of the supplementation of probiotic bacteria in the diet with inulin or dried Jerusalem artichoke tubers on the performance, meat quality, and fatty acid composition in the meat and backfat of fatteners. One hundred and forty-four crossbred pigs (PIC × Penarlan P76) were divided into six groups and fattened from 30 to 114 kg. The meat proximate composition, pH, color, texture, shear force, water-holding capacity, sensory attributes, and thiobarbituric-acid-reactive substances were measured. Normal post-mortem meat glycolysis was demonstrated and no meat defects were present. The chemical constituents in muscle tissues were similar, except for intramuscular fat (IMF). The addition of the prebiotics resulted in a higher IMF level, whereas a significantly lower content was found after the probiotic supplementation. Meat from both prebiotic groups was lighter, less red, and more yellow and showed a higher hue angle. The addition of both prebiotics significantly improved the antioxidant status of meat (by approximately 16% and 18%) and the water-holding capacity (less free water and higher M/T ratios), but reduced shear force (by 17%, p ≤ 0.05) and hardness (by 39% and 35%, respectively, p ≤ 0.05). The addition of the prebiotics and probiotics had no effect on any of the evaluated sensory attributes.